Lactobacillus paragasseri BBM171 Ameliorates Allergic Airway Inflammation Induced by Ovalbumin in Mice via Modulating the Th1/Th2 Balance - Shih-Hsuan Cheng; Tzu-Ying Yang; Chih-Chieh Hsu; Yu-Hsuan Wei; Chien-Chen Wu; Ying-Chieh Tsai (Microorganisms, 2022)
Supplementation with specific probiotics has been shown to improve allergic airway symptoms. This study aimed to investigate immunomodulatory effects of a potential probiotic strain isolated from breast milk, Lactobacillus paragasseri BBM171 (BBM171), in an ovalbumin (OVA)-induced allergic mouse model. OVA-sensitized and OVA-challenged BALB/c mice were orally administered live or heat-inactivated BBM171 for 48 consecutive days. After the last allergen challenge, serum immunoglobulin (Ig) levels, inflammatory cell levels in the lungs, and cytokine levels in bronchoalveolar lavage fluid (BALF) were assessed. The results showed that oral administration of live or heat-inactivated BBM171 decreased serum levels of total IgE, OVA-specific IgE, and OVA-specific IgG1, while increasing OVA-specific IgG2a and reducing the extent of airway inflammation in OVA-induced allergic mice. In addition, both live and heat-inactivated BBM171 modulated the cytokine profile in BALF to a type 1 T helper (Th1) response. Furthermore, ex vivo experiments using OVA-induced allergic mouse splenocytes showed that both live and heat-inactivated BBM171 could regulate the Th1/Th2 balance, decrease the proinflammatory cytokine interleukin (IL)-17 level, and increase the anti-inflammatory cytokine IL-10 level. Taken together, these results suggest that oral administration of live or heat-inactivated BBM171 improved allergen-induced airway inflammation symptoms by modulating the host immune response toward Th1 dominance.